RANCANG BANGUN BATTERY PACK LITHIUM 48 V 50 AH - Ariyanto, Nur Aidi; Fatkhurrozak, Faqih; Prasetio, Donny (Eksergi, 2022)
The electric vehicle is a vehicle with a driving source of an electric motor, requiring a battery for the stored energy. Battery packs are widely used as energy storage for electric vehicles. The battery pack is a series of several small batteries arranged in series and parallel so that they have an output voltage and capacity as required. 18650 Lithium battery is the most widely used to make battery packs and used on electric motorcycles. a 18650 Lithium battery has an output voltage of 3.7 V with various capacities such as 1500 mAh, 2000 mAh, 3000 mAh, etc. To design a 48 V 50 Ah battery pack requires a series of 18650 3.7 V 3000 mAh batteries which are arranged 13 pieces in series and 19 pieces in parallel. Before assembling, each 18650 battery must be checked for voltage, the voltage in each 18650 battery must be in the range of 3 ”“ 4.2 V. If it is less than 3 V then it needs to be recharged, if it is less than 2 V then the battery condition is not good. The battery pack discharging test is carried out by loading a BLDC 2000W 48V electric motor until the battery pack voltage drops to 39 V. The discharging process lasts for 13 hours with an average current of 3.5 A. From the test results, the battery pack capacity can be calculated, namely 45.5 Ah.